Trends in congenital heart disease mortality in the United States from 1968 to 2022 - Imran, Zahra; Khan, Taimor Mohammed; Waqas, Saad Ahmed; Ahmed, Raheel; Minhas, Abdul Mannan Khan (International journal of cardiology congenital heart disease, 2025)
Congenital heart disease (CHD) remains the leading cause of infant mortality due to birth defects in the United States. We analyzed long-term CHD mortality trends across age, sex, and racial groups from 1968 to 2022. We extracted CHD mortality data from the CDC WONDER database (1968–2022), using ICD-8/9/10 codes. Age-adjusted mortality rates (AAMRs) and crude mortality rates (CMRs) were calculated per 100,000 population. Joinpoint regression was used to assess temporal trends in mortality, reporting annual percentage changes (APCs) and average APCs (AAPCs) with 95 % confidence intervals (CIs). From 1968 to 2019, 234,658 CHD-related deaths were recorded. Overall AAMR declined from 3.2 (1968) to 0.8 (2019) per 100,000 (AAPC: −2.7 %; 95 % CI: −2.9 to −2.5). Males consistently had higher AAMRs than females. Racial disparities persisted, with slower declines among Black or African American individuals. Infants under 1 year accounted for 56.0 % of CHD deaths and showed the steepest mortality decline (AAPC: −3.2 %). Mortality rates plateaued in recent years. CHD mortality in the U.S. has declined markedly over the past five decades, though progress has slowed since 2009. Persistent disparities by race and sex emphasize the need for equitable access to specialized CHD care and ongoing public health efforts.